An overview of approaches for assessing the environmental sustainability of diets – a scoping review for Nordic Nutrition Recommendations 2023 - Tim G. Benton; Helen Harwatt; Anne Høyer-Lund; Helle Margrete Meltzer; Ellen Trolle; Rune Blomhoff (Food & Nutrition Research)
Assessing the environmental impacts of food, food systems and diets is highly complex due to the multitude of processes involved, the uncertainty in assessment models, the variability in production systems and the large range of products available. No single assessment method alone can provide a complete evidence base. The increasing number of Life Cycle Assessment and food system analyses, and more recently the integration of planetary boundaries offer insights from which we can draw some robust high-level conclusions, whilst recognising there is a need for more detailed analysis to capture the inherent nuances of more location and context-specific situations.Despite the complexity of assessing the environmental sustainability of food, diets and food systems, there are a number of key considerations that could be used to guide this process, and in doing so, they help to increase utility of the outcomes and limit unintended adverse consequences. We identified five key considerations that can be applied (consider the thresholds, consider the system, consider the variables, consider the context and consider the spillover) to ensure assessments are comprehensive.